2020
DOI: 10.1155/2020/8649868
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Control of a Photovoltaic Generator for Charging and Discharging Battery Using Adaptive Neuro-Fuzzy Inference System

Abstract: This paper presents a method of intelligent control of a photovoltaic generator (PVG) connected to a load and a battery. The system consists of charging and discharging a battery. An intelligent algorithm based on adaptive neuro-fuzzy inference system (ANFIS) is presented in this work. It performs two separate tasks simultaneously. First, it is used as a PVG Maximum Power Point Tracking (MPPT) command. This same algorithm is used secondly for protecting the battery against deep charges and discharges. A regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…One study showed that effective battery power management is possible with an ANFIS controller in a hybrid standalone system [28]. Some researchers worked on battery power control of photovoltaic generators with the ANFIS controller [29]. Another work is done on electric power swap between PEV and electrical grid by using ANFIS controller in smart grid [30].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that effective battery power management is possible with an ANFIS controller in a hybrid standalone system [28]. Some researchers worked on battery power control of photovoltaic generators with the ANFIS controller [29]. Another work is done on electric power swap between PEV and electrical grid by using ANFIS controller in smart grid [30].…”
Section: Introductionmentioning
confidence: 99%
“…Today's world sees rapid industry development and this makes us more energy dependent. Fossil sources occupy the largest share of electricity production [1], [2]. The use of conventional energies (around 87% of global energy consumption) has an undesirable impact on the environment in terms of greenhouse gas (GHG) emissions and safety (nuclear accidents).…”
Section: Introductionmentioning
confidence: 99%
“…The use of fossil resources inevitably reduces the reserves and compromises the energy future of the next generations. As a result, the global challenge is focused on renewable energies (solar, wind, hydro, geothermal, biomass,...) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the literature show that the Adaptive Neuro-Fuzzy Inference System (HNF) method is much more effective than the techniques usually used for MPP research. HNF has a very low response time and fewer oscillations around the MPP than other conventional methods [1]. In this work, the InC method is used for maximum power point tracking (MPPT) controller.…”
Section: Introductionmentioning
confidence: 99%